Variability in defence responses of rubber genotypes against Phytophthora meadii infections - Jayasuriya K E; Wijesundera R L C (Journal of the Rubber Research Institute of Sri Lanka, 2005)
DL
Keywords: Phytophthora leaf disease; PR-proteins; Tolerance